Smallholders' satisfaction toward the purchasing services of Sabah rubber industry board: The study in the district of Kota Belud - Mondin @ Ricky, Gimbun (2011)
Today's business world is completely based on customers' needs, wants and demands. That is the reason why many researchers and academicians have continuously emphasized on the importance of customer satisfaction. Most business organizations are now focusing on customer satisfaction to attain their goals and objectives. Their all efforts are to increase the value of customers and therefore growth and development of the business. In addition, the increasing level of competition compels the businesses to focus on the satisfaction of the customers toward their product or services. The purpose of this study is to gauge the level of satisfaction of rubber smallholders in the district of Kota Belud particularly the purchasing services provided by the Sabah Rubber Industry Board (SRIB) based on rubber price offering, purchasing schedules, attitudes of the Board's purchasing officers and the dissemination of rubber technology-related information to smallholders. At the same time, demographic factors are also found to have determine the smallholders’ interest towards the rubber industry. To achieve this purpose, the researcher hope that the findings of this study will help the management of the Sabah Rubber Industry Board (SIRB) to take necessary steps in increasing smallholders’ satisfaction towards establishing a long term synergistic profitable relationship between these two entities.